Effects of anthropogenic silt on aquatic macroinvertebrates and abiotic variables in streams in the Brazilian Amazon - Couceiro, Sheyla R.M.; Hamada, Neusa; Forsberg, Bruce Rider; Padovesi-Fonseca, Claudia (Journal of Soils and Sediments, 2010)
Purpose: While environmental risks associated with petroleum extraction such as oil spills or leaks are relatively well known, little attention has been given to the impacts of silt. The increase in petroleum exploitation in Amazonia has resulted in sediment input to aquatic systems, with impacts on their biodiversity. Here we use a combination of field measurements and statistical analyses to evaluate the impacts of anthropogenic silt derived from the construction of roads, borrow pits, and wells during the terrestrial development of gas and oil, on macroinvertebrate communities in streams of the Urucu Petroleum Province in the Central Brazilian Amazon. Material and methods: Ten impacted and nine non-impacted streams were sampled in January, April, and November of 2007. Macroinvertebrates were sampled along a 100-m continuous reach in each stream at 10-m intervals using a dip net. Abiotic variables including, a siltation index (SI), suspended inorganic sediment (SIS), sediment color index (SCI), suspend organic sediment (SOS), pH, electrical conductivity, dissolved oxygen, temperature, water velocity, channel width, and depth, were measured at three equidistant points in each stream (~30-m intervals). Results and discussion: SI did not differ between impacted and undisturbed streams. SIS was higher and SCI lower (more reddish) in impacted than in non-impacted streams. SCI had a positive and SIS a negative effect on both macroinvertebrate richness and density. SIS and SCI also influenced macrophyte taxonomic composition. In impacted streams, taxonomic richness and density were 1. 5 times lower than in non-impacted streams. No taxon was significantly associated with impacted streams. SIS was positively correlated with SOS and electrical conductivity while SCI was negatively correlated with SOS, electrical conductivity, and pH. The lack of difference in SI between impacted and non-impacted streams suggests that anthropogenic sediment does not accumulate on stream beds. The reddish color of SIS in impacted streams reflects terrestrial erosion and indicates the rapid flow of suspended sediments through these reaches, impacting macroinvertebrate richness, density, and species composition. Conclusions: Anthropogenic suspended silt has had a significant negative impact on aquatic macroinvertebrate diversity and density in streams in the Urucu Petroleum Province. Soil conservation measures are needed to reduce silt inputs and restore these streams to their natural condition. Additional studies are also needed to investigate the dynamics of sediments in the impacted streams. © Springer-Verlag 2009.
Keywords: Anthropogenic Effect; Aquatic Community; Biodiversity; Environmental Factor; Environmental Risk; Freshwater Ecosystem; Insect; Macroinvertebrate; Oil Spills; Petroleum Engineering; Road Construction; Silt; Soil Conservation; Species Richness; Suspended Load; Tropical Forest; Amazonia; Hexapoda